2015
DOI: 10.1016/j.mib.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil serine proteases in antibacterial defense

Abstract: Neutrophil serine proteases (NSPs) are critical for the effective functioning of neutrophils and greatly contribute to immune protection against bacterial infections. Thanks to their broad substrate specificity, these chymotrypsin-like proteases trigger multiple reactions that are detrimental to bacterial survival such as direct bacterial killing, generation of antimicrobial peptides, inactivation of bacterial virulence factors and formation of neutrophil extracellular traps. Recently, the importance of NSPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 49 publications
1
86
0
4
Order By: Relevance
“…This results in the accumulation of high levels of antimicrobial enzymes in the phagosome, with concentrations of MPO estimated to approach 1 mM (25). Concentrations in this range have also been proposed for NSPs (7,(26)(27)(28), which render the maturing phagosomal compartment not only highly oxidizing, but exceptionally digestive in character. In light of this, the dynamicallystructured nature of the SPIN N-terminal region suggested that it might be susceptible to proteolysis.…”
Section: The N-terminal Region Of Spin Is a Target Formentioning
confidence: 99%
“…This results in the accumulation of high levels of antimicrobial enzymes in the phagosome, with concentrations of MPO estimated to approach 1 mM (25). Concentrations in this range have also been proposed for NSPs (7,(26)(27)(28), which render the maturing phagosomal compartment not only highly oxidizing, but exceptionally digestive in character. In light of this, the dynamicallystructured nature of the SPIN N-terminal region suggested that it might be susceptible to proteolysis.…”
Section: The N-terminal Region Of Spin Is a Target Formentioning
confidence: 99%
“…In addition to AMP resistance, pathogenic bacteria have also developed mechanisms to evade targeting by other neutrophil granule constituents, including serine proteases such as neutrophil elastase, cathepsin G, proteinase 3, and neutrophil serine protease-4. The primary mechanisms of serine protease resistance used by bacterial pathogens are the modification of serine protease substrates and the production of serine protease inhibitors [43]. …”
Section: Bacterial Strategies To Evade Neutrophil Functionmentioning
confidence: 99%
“…NSPs are critical for the effective functioning of neutrophils and greatly contribute to immune protection against bacterial infections [27]. NSPs are currently believed to have three functions.…”
Section: Pathogen Killing By Neutrophilsmentioning
confidence: 99%